2016
DOI: 10.1007/s12178-016-9313-3
|View full text |Cite
|
Sign up to set email alerts
|

Total shoulder arthroplasty: are the humeral components getting shorter?

Abstract: Each generation of total shoulder arthroplasy has improved on the previous. The newest humeral component innovation is shortening the humeral component or eliminating the stem entirely to rely on stemless fixation in the humeral metaphysis. This offers theoretical advantages of preserved bone stock, less stress shielding, eliminating the diaphyseal stress riser, ease of stem removal at revision, and humeral head placement independent from the humeral shaft axis. There are a number of short term cohorts that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…This may result in massive bone loss, which requires complex revision surgery. The rationale of implants with metaphyseal fixation that are either stemless or have a short humeral stem is the facilitation of stem removal and preservation of bone in the event of revision surgery [11]. One other important aspect is the occurrence of stress shielding in longstem humeral components, which is associated with aseptic loosening and bone loss in the longer term [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may result in massive bone loss, which requires complex revision surgery. The rationale of implants with metaphyseal fixation that are either stemless or have a short humeral stem is the facilitation of stem removal and preservation of bone in the event of revision surgery [11]. One other important aspect is the occurrence of stress shielding in longstem humeral components, which is associated with aseptic loosening and bone loss in the longer term [16].…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to mimic native bone stress and to preserve bone in the case of revision surgery, design modifications led to the fourth generation of shoulder arthroplasty with stemless or short-stem humeral components aimed at metaphyseal fixation [7,11,14]. In 2016, Harmer et al performed a systematic review of stemless and short-stem shoulder prosthesis and found that only one study reported results of anatomical shoulder replacement with an uncemented short stem [11]. The authors therefore concluded that longer-term and betterdesigned studies are needed if short stems and stemless components are to become the gold standard for care.…”
Section: Short-stem Anatomical Shoulder Replacement-a Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent review articles, the overall complication rate lies between 4.2% and 15.2%[ 14 , 15 ]. In the literature, an arthrofibrosis after shoulder arthroplasty is rarely documented[ 15 , 16 ], whereas a rotator cuff failure is reported with incidences between 1.3% and 14%[ 17 - 19 ] and a plexus lesion with incidences up to 15%[ 20 , 21 ]. Taken together, our complication rate is high and lies in the upper range compared to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Humeral stems have gone through many design adaptations, from first-generation cemented Neer stems with a unique geometry in five sizes of increasing diameters, to fourth-generation uncemented humeral stems, featuring short and stemless designs. 28 Cemented long stems, which were the norm from the late 1970s to the early 2000s, largely improved in function and pain, 4,29 but their revision rate is around 10% at ten years and 20% to 30% at 20 years. 7,30 Our review revealed overall stem revision rates of 9% to 14% at 10 to 20 years for uncemented uncoated long designs.…”
Section: Discussionmentioning
confidence: 99%